ADVANCED MATHEMATICS FORM 6 – DIFFERENTIAL EQUATION

Share this post on:

First order homogenous D.E

          In first order H.D.E all the terms are of the same dimension

Consider the table about dimensions

Term X x2 1/x xn 3 y yn x2/y x2y
Dimension 1 2 -1 n O 1 N 1 3

 

dy/dx dy2/dx2 xdy/dx yx  
  0   1 2  

 

edu.uptymez.com

O shows there is no effect on the term

Which of the following equation are first order homogeneous

a) x2 edu.uptymez.com = y2

b) xy edu.uptymez.com = x2 + y2

c) x2
edu.uptymez.com = 1 + xy

d) (x2
edu.uptymez.com = edu.uptymez.com

e) (x2 – y2) edu.uptymez.com = 2xy

f) (1 + y2) edu.uptymez.com = x

Solution of 1st order Homogeneous  differential equation

1st order homogeneous d.e can be written in the form edu.uptymez.com = Q

Where both P and Q are function of and have same dimension.

Suppose p and Q hence the dimension

          Then divide by xn and use the substitution

          Y = vx =      v = edu.uptymez.com

          i.e edu.uptymez.com

Example 1.

Solve edu.uptymez.com = edu.uptymez.com

Solution

   Since all terms are of degree 2, i.e the equation is homogeneous

          Let y = vx

          edu.uptymez.com = v + edu.uptymez.com

          And

                   edu.uptymez.com = edu.uptymez.com

                           = edu.uptymez.com (edu.uptymez.com)

                             = edu.uptymez.com

                   V + edu.uptymez.com = edu.uptymez.com

                             edu.uptymez.com = edu.uptymez.com – v

                             = edu.uptymez.com

                             edu.uptymez.com = edu.uptymez.com

                             edu.uptymez.com = edu.uptymez.com

          edu.uptymez.com = edu.uptymez.com dx

            edu.uptymez.com = lnx + c

But v = edu.uptymez.com

   edu.uptymez.com2 = ln x + c

          edu.uptymez.com = lnx + c

          Y2 = 2x2 (lnx + c)

Example 2

Solve xyedu.uptymez.com = x2 + y2

          Solution

          All terms are of the order 2

          xy edu.uptymez.com = x2 + y2……

          Let y = vx

          edu.uptymez.com = v + edu.uptymez.com

          From the equation…

          edu.uptymez.com = edu.uptymez.com + edu.uptymez.com

          But y = vx

          = edu.uptymez.com = edu.uptymez.com + edu.uptymez.com

                   = x2
edu.uptymez.com

                     = edu.uptymez.com

          V + edu.uptymez.com = edu.uptymez.com

                   edu.uptymez.com = edu.uptymez.com

                         = edu.uptymez.com

                   edu.uptymez.com = edu.uptymez.com

                   edu.uptymez.com = edu.uptymez.com

                   edu.uptymez.com = lnx + A

                   But v = edu.uptymez.com

                   edu.uptymez.com2 = lnx + A

                   Y2 = 2x2 (lnx + A)

Example 3

Solve the following

(x2 + xy) edu.uptymez.com = xy – y2

            Solution

     edu.uptymez.com

          Let y = vx

          edu.uptymez.com = v + edu.uptymez.com

          And

          edu.uptymez.com = edu.uptymez.com

                   = edu.uptymez.com

                   v + edu.uptymez.com = edu.uptymez.com

                   edu.uptymez.com = edu.uptymez.com-v

                   = edu.uptymez.com

                   =edu.uptymez.com

          edu.uptymez.com = edu.uptymez.com

          edu.uptymez.com[(edu.uptymez.com dv + edu.uptymez.com dv)] = edu.uptymez.com

          –½ (edu.uptymez.com + ln v) = lnx + c

     edu.uptymez.com

          edu.uptymez.com = ln (x2 V) + 2c

          But v = edu.uptymez.com

          edu.uptymez.com = ln (x2edu.uptymez.com) + 2c

          edu.uptymez.com – 2c = ln (x2.edu.uptymez.com)

          Let ln A = -2c

          edu.uptymez.com + ln A = ln xy

      edu.uptymez.com
Xy = Aex/y

          EXERCISE

Solve the differential equation

1.  x2 edu.uptymez.com = y (x + y)

2. (x2 + y2) edu.uptymez.com = xy

First order exact differential equation

We know that edu.uptymez.com

Now consider

          edu.uptymez.com + y = ex

Integrating both side w.r.t.x

          = xy = e2 + c

                   Y = edu.uptymez.com (ex + c)

                   Y = edu.uptymez.com (ex + C)

2.  Find the general solution of the following exact differential equation.

          i)exy + exedu.uptymez.com = 2

        ii) cos xedu.uptymez.com – ysin x = x2

          Solution

          i) Given

        edu.uptymez.com

                   edu.uptymez.com (exy) = 2

          Integrating both sides with respect to x

                   edu.uptymez.com (exy) dx = edu.uptymez.com

                 edu.uptymez.com

          ii) Given

                   cosx edu.uptymez.com – y sin x = x2

                   edu.uptymez.com (y cos x) = x2

          Integrating both side with respect to x

          = edu.uptymez.com (exy) dx = edu.uptymez.com

                   Y cos x = edu.uptymez.com + c

                   3ycosx = x3 + 3C

                   3ycosx = x3 + 4

3.      edu.uptymez.com edu.uptymez.com + lny = x + 1

                   Soln

                   Given edu.uptymez.com edu.uptymez.com + lny = x + 1

          Integrating both sides w.r.t x

          edu.uptymez.com (x ln y) dx = edu.uptymez.com

                   Xln y = ½ x2 + x + C

                   2xlny + x2 + 2x + 2c

                   2x lny + x2 + x + A

          Integrating factors

          Consider first order differential equation of the form

                   edu.uptymez.com + py =Q

          Where p and Q are functions of x

          Multiplying by integrating factor F both sides will make an exact equation

          i.e F edu.uptymez.com + Fpy + FQ…….i

                   edu.uptymez.com = edu.uptymez.com + edu.uptymez.com

                   edu.uptymez.com + edu.uptymez.com…..ii

          Comparing (i) (ii)

          edu.uptymez.com + Fpy = edu.uptymez.com + edu.uptymez.com

                        Fpy = edu.uptymez.com

                   edu.uptymez.com = Fp

                   edu.uptymez.com dF = edu.uptymez.com by separating of variables
edu.uptymez.com
F = edu.uptymez.com is the required integrating factor

Examples

1. Solve edu.uptymez.com + y = x3

            Solution

                   edu.uptymez.com + y = x3

                   edu.uptymez.com + edu.uptymez.com = x2

          Compare with edu.uptymez.com + py = Q

                             P = edu.uptymez.com

                   Then edu.uptymez.com = edu.uptymez.com dx

                                      = ln x

                   If F = eln x

                   F       = eln x

                   edu.uptymez.com (xy) = x2 x

                   edu.uptymez.com (xy) = edu.uptymez.com

                   Xy = edu.uptymez.com x4 + C

2. Solve

          (x + 1) edu.uptymez.com + y + (x + 1)2

            Soln

                   (x + 1) edu.uptymez.com + y + (x + 1)2

                   = edu.uptymez.com + edu.uptymez.com = x + 1

                   = edu.uptymez.com +edu.uptymez.com , y = x + 1

          P = edu.uptymez.com

          edu.uptymez.com

          F = esp

             = eln (x + 1)

              = x + 1

          Y (x + 1) = edu.uptymez.com

                   = edu.uptymez.com

          = edu.uptymez.comx3 + x2 + x + c

          = edu.uptymez.com + c

          Y = edu.uptymez.com + edu.uptymez.com

3.      Solve (1 – x2) edu.uptymez.com – xy = 1

          Solution  edu.uptymez.com – edu.uptymez.com y = edu.uptymez.com

                   P = edu.uptymez.com

                   edu.uptymez.com = edu.uptymez.com dx

                             = ½ ln (1 – edu.uptymez.com)

                             F = e ln (1edu.uptymez.com ½

                                     = (1 – x2) ½

                   Y edu.uptymez.com = edu.uptymez.com edu.uptymez.com dx

                                      = edu.uptymez.com dx

                   Y = edu.uptymez.com

4.      tanx edu.uptymez.com + y = ex tan x

          Solution

                   edu.uptymez.com +edu.uptymez.com , y = ex

                   P = edu.uptymez.com = cot x

                   edu.uptymez.com = edu.uptymez.com

                             = ln edu.uptymez.com

                             F = eln edu.uptymez.com

                             =edu.uptymez.com

                   Y edu.uptymez.com= edu.uptymez.com dx

          Integrating by parts the R.H.S

= edu.uptymez.com = ex
edu.uptymez.comedu.uptymez.com edu.uptymez.comdx

                   = ex sin x – (ex cos x + edu.uptymez.com edu.uptymez.comdx

                   = ex
edu.uptymez.com– ex
edu.uptymez.comedu.uptymez.com edu.uptymez.comdx

          2edu.uptymez.com sin x dx = e x (edu.uptymez.com –edu.uptymez.com)

                   edu.uptymez.com = edu.uptymez.com (edu.uptymez.com)

                   Y sin x = edu.uptymez.com (edu.uptymez.com) + c

Bernoulli’s equation

This is a first order D.E of the form

          edu.uptymez.com + p (x) y = Q (x) y n

 edu.uptymez.com p (x) and Q (x) are functions of x or constant

Steps

          edu.uptymez.com + p (x) y = Q (x) yn……i

          Divide both sides by yn gives

          Y-n edu.uptymez.com  + p (x) y1 – n = Q (x)…… (ii)

          Let z = y1-n

          (1 – n) y-n edu.uptymez.com

Multiplying (ii) by (1 – n) both sides gives

          (1edu.uptymez.com – n) y-n edu.uptymez.com  + (1 – n) p (x) y (1 – n) = (1 – n) Q (x)

          edu.uptymez.com + (1 – n) p (x) y (1 – n) = (1 – n) Q (x)

          edu.uptymez.com + p1 (x) y (1 – n) = Q1 (x)

 edu.uptymez.com p1 (x) and Q1 (x) are functions of x or constant

          But z = y (1 -n)

          = edu.uptymez.com + p1 (x) z = Q1 (x)……..ii

iii) is linear the use of integrating  factor  can be used

Example 1

Solve edu.uptymez.com + edu.uptymez.com = xy2

Solution

edu.uptymez.com 

Dividing both sides by edu.uptymez.com gives

edu.uptymez.com 

Let Z = edu.uptymez.com

edu.uptymez.com 

Multiply (ii) by -1 gives

edu.uptymez.com 

edu.uptymez.com 

But Z = edu.uptymez.com

edu.uptymez.com 

edu.uptymez.com 

edu.uptymez.com 

               = edu.uptymez.com

               = edu.uptymez.com

edu.uptymez.com 

edu.uptymez.com 

= edu.uptymez.com

Then Z.F= edu.uptymez.com

edu.uptymez.com 

       = -1edu.uptymez.com

       = edu.uptymez.com

But Z = edu.uptymez.com

edu.uptymez.com 

edu.uptymez.com 

edu.uptymez.com 

Example 2

Solve edu.uptymez.com

Solution

1st Expressing the equation in the form

edu.uptymez.com 

–         edu.uptymez.com

–         edu.uptymez.com

Let Z = edu.uptymez.com

edu.uptymez.com 

edu.uptymez.com 

edu.uptymez.com 

But Z = edu.uptymez.com

edu.uptymez.com 

edu.uptymez.com 

edu.uptymez.com 

            = edu.uptymez.com

            = edu.uptymez.com

edu.uptymez.com 

edu.uptymez.com 

Then

edu.uptymez.com 

edu.uptymez.com 

edu.uptymez.com 

         edu.uptymez.com 

But Z = edu.uptymez.com

edu.uptymez.com 

Example 3

Solve edu.uptymez.com

Solution

Expressing the equation in the form

edu.uptymez.com 

edu.uptymez.com 

Then dividing by edu.uptymez.com

edu.uptymez.com 

let  Z = edu.uptymez.com

edu.uptymez.com 

Multiply (ii) by -2 gives

edu.uptymez.com 

edu.uptymez.com 

But Z = edu.uptymez.com

edu.uptymez.com 

edu.uptymez.com 

edu.uptymez.com 

edu.uptymez.com 

edu.uptymez.com 

edu.uptymez.com 

Then,  edu.uptymez.com 

           edu.uptymez.com 

          edu.uptymez.com

          edu.uptymez.com

 But Z = edu.uptymez.com

edu.uptymez.com 

Exercise

Solve the following first order D.es

1.     edu.uptymez.com

2.     edu.uptymez.com

Share this post on: